TRANSFORMATIVE DA'WAH FOR GEN-Z IN THE ERA OF DISRUPTION - Hidayat, Mokh. Ulil (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2025)
The era of disruption has brought fundamental changes in communication patterns and religious practices, especially for Generation Z (Gen-Z) who grew up in digital culture. Islamic da'wah faces new challenges in the form of fragmentation of authority, instant culture, and the penetration of transnational ideologies through social media. This article aims to analyze the reality of Islamic da'wah in Gen-Z in the era of disruption, their interaction patterns with religion and digital da'wah content, and formulate transformative da'wah concepts that are relevant to the characteristics of this generation. Using a qualitative approach based on literature review and netnography methods, this study found that Gen-Z interacts with religion selectively, pragmatically, and participatically through digital spaces, although they are vulnerable to simplification of meaning and penetration of extreme beliefs. The concept of transformative da'wah is offered as an alternative strategy that integrates theological depth, dialogical pedagogy, the use of adaptive digital media, and social praxis orientation. The results of the study show that transformative da'wah not only demands the use of digital technology, but also the strengthening of scientific authority, psychological assistance, and participatory mechanisms that allow the internalization of Islamic values in Gen-Z social practices. Thus, transformative da'wah can be a relevant, ethical, and sustainable model of da'wah in the era of disruption.